"Birth of the (bio)police": what can Foucault teach us about the police? - Cavalcanti da Silva, Marcio Roberto; Cozza Sayão, Sandro; da Silva Lira, João Jânio (Ius Humani. Jornal do direito, 2025)
This paper investigates the concept of police in the political writings of the French philosopher Michel Foucault. Considering in particular his work Security, territory, population (1977-1978), we intend to analyze the thesis that modern governmentality enabled the formation of "political technologies of individuals", on whose foundation the control of territory and population are connected. By passing the readings of Discipline and punish (1975), which reduces the police to the image of vigil and punishment, and encompassing the ideas developed in Foucault's biopolitical program, the concept of police gains new contours and depth when considered within a history of governmentality. In this sense, here the concept of police will be appreciated as the "means" through which the generalization of bios through biopolitics was promoted. The sustained hypothesis is that the archaeogenealogical foundations through which the police came to be established in modernity allowed us to think of the police beyond the vigilant and punitive image, but as a mechanism subject to biopower, thus allowing us to define them as (bio)police. Thus, this research shows Foucault's in-depth reflections on the birth of the modern police and its relationship with biopolitics, proposing a new reading in the concept of policy inside Foucauldian thinking. In the meantime, the concept of the (bio)police is defined to account for the "treatise on the police" developed by Foucault in addition to the work Discipline and punish.